Gender-transformative health promotion interventions for linking and retaining tuberculosis-diagnosed adult men in care in sub-Saharan Africa: A scoping review protocol - Siyabonga Kave; Yandisa Sikweyiya; Nelisiwe Khuzwayo (PLoS ONE, 2026)
Tuberculosis (TB) remains a leading cause of infectious disease mortality globally, with men in sub-Saharan Africa (SSA) disproportionately affected. Men experience higher TB incidence, delayed care-seeking, poorer treatment adherence, and elevated mortality compared to women. Gender-transformative health promotion interventions that challenge harmful masculine norms, enhance health system responsiveness, and foster positive health behaviours show promise for improving linkage to and retention in TB care. However, evidence on their design, implementation, and effectiveness in SSA is limited. Following the Arksey and O’Malley framework, refined by Levac et al., this scoping review will map evidence on gender-transformative health promotion interventions targeting adult men (≥18 years) diagnosed with any form of TB in SSA. We will search PubMed via MEDLINE, the Cochrane Library, Embase.com, Global Health, Web of Science, PsycINFO, Google Scholar, Africa-Wide Information, and the WHO Library, and screen reference lists of included studies. Eligibility will follow the Population–Concept–Context (PCC) framework, focusing on interventions supporting linkage to care, treatment initiation, adherence, or retention in care. Data will be charted using a standardized extraction tool, quality appraised using the Mixed Methods Appraisal Tool, and narratively synthesized using the RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) framework. Stakeholder consultations will inform the interpretation of findings. As a protocol, no results are reported. The review will identify intervention characteristics, implementation strategies, barriers, facilitators, and outcomes across SSA contexts. Findings will guide the development of culturally sensitive, gender-responsive TB interventions aligned with the Sustainable Development Goal 3 to improve linkage and retention among men diagnosed with TB in SSA.